2019
DOI: 10.1007/s13300-019-00701-3
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Empagliflozin in Comparison to Sitagliptin and Saxagliptin Based on Cardiovascular Outcome Trials in Patients with Type 2 Diabetes and Established Cardiovascular Disease

Abstract: IntroductionIn the cardiovascular outcome trials (CVOT) EMPA-REG OUTCOME, TECOS and SAVOR-TIMI 53, empagliflozin [sodium/glucose cotransporter 2 (SGLT2) inhibitor], sitagliptin and saxagliptin [both dipeptidyl peptidase 4 (DPP4) inhibitors] + standard of care (SoC) were compared to SoC in patients with type 2 diabetes and established cardiovascular disease (CVD). This study assessed the cost-effectiveness (CE) of empagliflozin + SoC in comparison to sitagliptin + SoC and saxagliptin + SoC based on the respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 37 publications
5
25
0
Order By: Relevance
“…In addition, given the recent increase in diabetes incidence at a younger age due to lifestyle changes, 114 the actual earnings and expenses affected by the reduction or cessation of work productivity should also be evaluated. In parallel with several successful RCT results showing a risk reduction of cardiovascular and renal events with SGLT2i in patients with T2DM, several studies using a simulation model suggested better cost‐effectiveness of SGLT2i compared to that of non‐SGLT2i treatment when used in addition to the standard of care 115–121 . Moreover, an observational study using a database in the US and Sweden demonstrated lower healthcare costs of SGLT2i initiation compared to those of DPP4‐i or other non‐SGLT2i treatments 122,123 .…”
Section: Recent Diabetes Studies In Japanmentioning
confidence: 85%
“…In addition, given the recent increase in diabetes incidence at a younger age due to lifestyle changes, 114 the actual earnings and expenses affected by the reduction or cessation of work productivity should also be evaluated. In parallel with several successful RCT results showing a risk reduction of cardiovascular and renal events with SGLT2i in patients with T2DM, several studies using a simulation model suggested better cost‐effectiveness of SGLT2i compared to that of non‐SGLT2i treatment when used in addition to the standard of care 115–121 . Moreover, an observational study using a database in the US and Sweden demonstrated lower healthcare costs of SGLT2i initiation compared to those of DPP4‐i or other non‐SGLT2i treatments 122,123 .…”
Section: Recent Diabetes Studies In Japanmentioning
confidence: 85%
“…The study demonstrated that empagliflozin plus standard care is a cost-effective treatment compared with only standard care and was considered dominant versus liraglutide plus standard care in the management of patients with both diabetes and confirmed CVD [ 45 ]. In other health economic studies based on the EMPA-REG OUTCOME trial, it has also been confirmed that empagliflozin therapy is cost-effective in patients with both diabetes and confirmed CVD [ 46 – 48 ].…”
Section: Sglt2 Inhibition and Clinical Outcomesmentioning
confidence: 90%
“…Previous treatment‐sequence cost‐effectiveness analyses in T2D have been reported, although not with sequences that compared empagliflozin with sitagliptin 27,28 . In a previous analysis that did compare empagliflozin plus standard of care (SoC) with sitagliptin plus SoC, sequences were not considered and only patients with established CVD were modelled 29 . Nonetheless, similar trends were observed in that study, as empagliflozin plus SoC was found to be cost‐effective compared with sitagliptin plus SoC (£6464/QALY) 29 .…”
Section: Discussionmentioning
confidence: 99%
“…In a previous analysis that did compare empagliflozin plus standard of care (SoC) with sitagliptin plus SoC, sequences were not considered and only patients with established CVD were modelled 29 . Nonetheless, similar trends were observed in that study, as empagliflozin plus SoC was found to be cost‐effective compared with sitagliptin plus SoC (£6464/QALY) 29 . In another study, although a comparison of empagliflozin and sitagliptin was not presented, the absolute cost and QALY results indicate that empagliflozin is cost‐effective versus sitagliptin (an ICER of $37 500/QALY was calculated based on the reported results) 30 .…”
Section: Discussionmentioning
confidence: 99%